Triruthenium clusters containing vinyl ligands: synthesis and structure of Ru-3(mu(2)-CO)(2)(CO)(6)[mu(3)-NS)(O)MePh](mu(2)-eta(1),eta(2)-PhCH2C=CH 2), Ru-3(mu(2)-CO)(CO)(7)[mu(3)-NS(O)MePh](mu(3)-eta(1),eta(2)-(PrC)-C-n=CHP rn), Ru-3(mu(2)-CO)(CO)(7)[mu(3)-NS(O)MePh](mu(3)-eta(1),eta(2)-PhC=CHBun), and (mu(2)-H)Ru-3(CO)(6)(mu(2)-eta(1),eta(2)-PhC=CHPh)(mu(3)-eta(1),eta(2)-P hC CPh)[mu(3)-eta(1),eta(2)-NS(O)Me(C6H4)] - Ferrand, Vincent; Merzweiler, Kurt; Rheinwald, Gerd; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 1997)
The electron-deficient cluster (mu(2)-H)Ru-3(CO)(9)[mu(3)-NS(O)MePh] (1) reacts with the terminal alkyne PhCH2C=CH to give the vinyl complex Ru-3(mu(2)-CO)(2)(CO)(6)[mu(3)-NS(O)MePh](mu(2)-eta(1),eta(2)-PhCH2C=CH2 ) (2). The analogous reaction with internal alkynes (RC=CR') affords the clusters Ru-3(mu(2)-CO)(CO)(7)[mu(3)-NS(O)MePh](mu(3)-eta(1),eta(2)-RC=CHR') (3: R = R' = Pr "; 4: R = Ph; R' = Bu ") in which the vinyl ligand has opened a Ru-Ru bond upon coordination the Ru-3 framework. In the case of diphenylacetylene, reaction with two equivalents of the alkyne, yields the vinyl-alkyne cluster (mu(2)-H)Ru-3(CO)(6)(mu(2)-eta(1),eta(2)-PhC=CHPh)(mu(3)-eta(1),eta(2)-P hC=CPh)[mu(3)-eta(1),eta(2)-NS(O)Me(C6H4)] (5) with ortho-metallation of the phenyl substituent of the sulfoximido cap. (C) 1997 Elsevier Science S.A.
Keywords: clusters; ruthenium; alkynes; vinyl ligands; crystal structures; CARBONYL CLUSTER; = 2-AMINO-6-METHYLPYRIDINE; CATALYTIC ACTIVITY; CRYSTAL-STRUCTURES; ANCILLARY LIGANDS; X-RAY; COMPLEXES; ALKYNE; HYDROGENATION; DIPHENYLACETYLENE